Semantik eine Einführung - Löbner, Sebastian 1949- (De Gruyter Studium, 2015)
The book offers an up-to-date introduction to the essential phenomena, issues, and theoretical approaches of linguistic semantics. It covers the key aspects of word and sentence semantics. In his step-by-step development of the theme, the author puts great stock in the consistency, coherence, and understandability of the scientific approach. The new edition has been extensively revised, expanded, and updated